PWE-122 Non-Bowel Cancer Screening Colonoscopy HasInferior Rates of Polyp Retrieval and Adenoma Detection than Bowel Cancer Screening. (17th August 2016) - Sehgal, V; Jones, TN; Ping, LLY; Robbins, A; Edwards-Bailey, A; Belón, LA; Rodriguez-Justo, M; Besherdas, K
Abstract : Introduction: Colonoscopy within the Bowel Cancer Screening Programme (BCSP) is scrutiny to high national standards and enhanced quality assurance. These include accredited colonoscopists who are required to have passed a summative assessment and perform more than 150 BCSP colonoscopies annually. Additionally, extended time allocation to allow for longer withdrawal times, are thought to further improve quality. In contrast, patients attending for non-BCSP (NBCSP) may have their colonoscopy performed by any endoscopist with less time allocation. Adenoma detection rate (ADR) a key quality indicator of colonoscopy with the strongest association to post-colonoscopy colorectal cancer. We hypothesised that patients within the BCSP had a superior ADR to NBCSP patients and consequently, a higher quality colonoscopy. Methods: Patients attending for BCSP and NBCSP colonoscopy over a 2 year period (August 2013–July 2015) at University College London Hospital were identified. NBCSP patients aged 60–74 years were only included in our analyses. BCSP colonoscopy was performed by one of 6 BCSP accredited colonoscopists. NBCSP colonoscopy was performed either by a nurse endoscopist, registrar (including those in training) or a consultant. An in-house endoscopy and BCSP database were used to record polyp detection (PDR), polyp retrieval (PRR), adenoma to polyp detection rate (APDR) and adenoma detection rates (ADR) in both groups. The Student's t-test was used and p < 0.05 was statistically significant. Results: A total of 1, 547 and 5, 898 patients attended for BCSP and NBCSP colonoscopy. In the NBCSP group, 1, 692 (29%) were aged 60–74 years and were only included in our analyses. The polyp detection rate (PDR) in the BCSP group was significantly higher (931/1547, 60%) than in the NBCSP group (465/1692, 27%), p < 0.05. In the BCSP group, a total of 2, 094 polyps were removed. In the NBCSP group, 1, 048 polyps were removed. The PRR was significantly higher in the BCSP patients (2086/2094, 99%) compared to NBCSP patients (764/1048, 76%), p < 0.001. The APDR was similar between both groups - BCSP 1, 542/2, 086 (74%), NBCSP 572/764 (75%). In contrast, the ADR was significantly higher in the BCSP cohort (735/1547 patients had >=1 adenoma, 48%) compared to the NBCSP group (337/1692 patients had >=1 adenoma, 20%), p < 0.05. Conclusion: To our knowledge, this is one of the largest multi-operator studies comparing quality indicators in BCSP and NBCSP patients. Our study has demonstrated that NBCSP patients are more likely to have a significantly lower PRR and ADR than their BCSP counterparts. Further efforts should be made to address this disparity to help drive equality between these two services. Disclosure of Interest: None Declared